Headstarting Turtles—Is it a Valid Strategy for Wildlife Rehabilitators? - Forrester, Harriet (Wildlife Rehabilitation Bulletin, 2006)
Headstarting is the hatching and rearing of turtles in captivity until they reach a size that will discourage predation. Headstarted turtles may be kept in captivity from several months to a few years before they are released. There are two purposes: to boost populations, and/or to establish new nesting sites (most often used with sea turtles). Although some have argued that headstarting turtles increases their chances for survival, others believe that headstarting is useless if it does not address other causes of species decline. In some cases, it may actually be harmful to turtles.